DESIGN DEVELOPMENT AND ANALYSIS OF QUARTER CAR TEST RIG FOR MEASUREMENT OF TYRE PRESSURE WITH DIFFERENT CONDITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Under or over Inflated tyres increases rolling resistance, which not only reduces fuel economy, but can also wear out tyres and reduce vehicle safety through poor handling. Maintaining correct tyre pressures and monitoring for uneven tyre wear (which can be caused by poor wheel alignment) can help to ensure optimum vehicle performance. For testing of automatic tyre inflation sytem we designed a quarter car (Single wheel) test rig with condition of traction change, speed change and road condition variance to determine the damping parameter provided by the air pressure in tyre.